+0  
 
0
352
4
avatar+2442 

2 q's- please help, ty!

 Apr 26, 2018

Best Answer 

 #1
avatar+5258 
+3

Question 1: Simplify the expression: \((2-3i)(4+2i)\)

 

For this, we'll use the FOIL method.

 

2*4=8

 

8+__+__+__

 

2*2i=4i

 

8+4i+__+__

 

-3i*4=-12i

 

8+4i-12i+__

 

-3i*2i=-6i2

(I'm assuming i=sqrt(-1))

 

8+4i-12i+6=14-8i

 

Option S is your answer

 

Question 2: Simplify the expression: \((3x^4+9x^3-7x+15)+(-6x^4-8x^2+5x-3)\)

 

This is adding like terms.

 

First, let's start with x^4

 

3-6=-3

 

-3x4+9x3-8x2+__+__

 

There were only one x^3 and x^2 in the expression, so we know that part for sure.

 

Now, to the x term.

 

-7+5=-2

 

-3x4+9x3-8x2-2x+__

 

Now, to the normal numbers.

 

15-3=12

 

Final answer: -3x4+9x3-8x2-2x+12

 

Hope this helped!

 Apr 26, 2018
edited by rarinstraw1195  Apr 26, 2018
 #1
avatar+5258 
+3
Best Answer

Question 1: Simplify the expression: \((2-3i)(4+2i)\)

 

For this, we'll use the FOIL method.

 

2*4=8

 

8+__+__+__

 

2*2i=4i

 

8+4i+__+__

 

-3i*4=-12i

 

8+4i-12i+__

 

-3i*2i=-6i2

(I'm assuming i=sqrt(-1))

 

8+4i-12i+6=14-8i

 

Option S is your answer

 

Question 2: Simplify the expression: \((3x^4+9x^3-7x+15)+(-6x^4-8x^2+5x-3)\)

 

This is adding like terms.

 

First, let's start with x^4

 

3-6=-3

 

-3x4+9x3-8x2+__+__

 

There were only one x^3 and x^2 in the expression, so we know that part for sure.

 

Now, to the x term.

 

-7+5=-2

 

-3x4+9x3-8x2-2x+__

 

Now, to the normal numbers.

 

15-3=12

 

Final answer: -3x4+9x3-8x2-2x+12

 

Hope this helped!

rarinstraw1195 Apr 26, 2018
edited by rarinstraw1195  Apr 26, 2018
 #2
avatar+5258 
+2

EDIT: Included Question 2

rarinstraw1195  Apr 26, 2018
 #3
avatar+98196 
+1

Thanks, Rarinstraw  !!!

 

 

cool cool cool

CPhill  Apr 26, 2018
 #4
avatar+2442 
+2

Tysm! :D

RainbowPanda  Apr 26, 2018

27 Online Users

avatar
avatar